The role of arbitration in the resolution of international commercial disputes - Eishan Jan, Mohammad Naqib (International Islamic University Malaysia, 2014)
There are several methods of dispute resolution which are available to parties in international commercial contracts. However, arbitration has been enjoying overwhelming patronage and dominance over all other dispute resolution methods that are at the disposal of disputants. The article examines the role of arbitration in the resolution of international commercial disputes with a view to portraying its significance in the resolution of commercial disputes that have certain foreign elements. In doing so, the article considers the arbitration agreement, how it features in commercial contracts and the necessary elements for its recognition and enforceability. The articlefurther examines the factors responsible for the significant role of arbitration and its prevalence in the resolution of international commercial disputes. In view of such task and in order to critically bring out the attractive role of arbitration, the article discusses advantageous features of arbitration such as the parties’ freedom, neutrality of the arbitrators, the applicable law and the seat of arbitration, flexibility of the process, confidentiality and transnational enforcement of awards. In view of these merits, it is recommended that parties to international commercial transactions should have an arbitration agreement in their contracts in order to allow reference to arbitration in resolving their future commercial disputes.